2015
DOI: 10.3844/ajeassp.2015.748.766
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Design of Masonry and Reinforced Concrete Infilled Frames: A Comprehensive Overview

Abstract: Despite the extensive research on the seismic behavior of infilled frames since 1960's, there is no general consensus towards a unified approach. Purpose of this study is to review the existing analytical and experimental research, as well as code provisions, on masonry and on reinforced concrete infilled frames. The basic characteristics of infilled frames and how these affect seismic performance are summed up. Different approaches of the equivalent strut, broadly used for modeling of the infilled frames, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Another article studying the seismic behavior of vertical shear links made of easy-going steel must be essentially mentioned (Daryan et al, 2008). Last but not least, the following paper is of extreme importance as it gives a comprehensive overview about the seismic design of masonry and reinforced concrete infilled frames (Moretti, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another article studying the seismic behavior of vertical shear links made of easy-going steel must be essentially mentioned (Daryan et al, 2008). Last but not least, the following paper is of extreme importance as it gives a comprehensive overview about the seismic design of masonry and reinforced concrete infilled frames (Moretti, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Experimental studies have shown that behavior of an infilled frame is heavily influenced by interaction of the infill with its bounding frame (Al-Chaar et al, 2002;Dias, 2007;Kakaletsis and Karayannis, 2008;Shing, 1997, 2003;Shing et al, 1994). The Gap between infill and surrounding frame was found to be the most important parameter affecting the infill-frame behavior and unless this gap was not closed, the masonry infill contributed poorly to the lateral in-plane behavior of the frame (Moretti, 2015;Schmidt, 1989). Apart from the experimental investigations, a number of different analytical models (micro-and macro-models) have been developed to evaluate the infilled structures.…”
Section: Introductionmentioning
confidence: 99%
“…Macro-models, first proposed by Smith (1966), use the idea of equivalent strut at the compressed diagonal. There are many empirical approaches to determine the effective width of a single equivalent strut (Goutam and Sudhir, 2008;Kakaletsis and Karayannis, 2008;Raghavendra et al, 2014) or multi-struts (Asteris et al, 2011;Lavanya et al, 2015;Moretti, 2015;Zybaczynski, 2014). The second class of analytical models, generically named as micro-models, relies on complex analysis using the finite element method (FEM) investigated by several researchers starting with Mallick and Garg (1971), Liauw (1972), Page (1978), Lotfi (1992), Shing et al (1994), Riddington and Naom (1993), Shing (2008, 2012), Al-Chaar and Mehrabi (2008), Koutromanos et al (2011), Syed et al (2012), Kadid et al (2013), and Pavone (2014).…”
Section: Introductionmentioning
confidence: 99%
“… Aly and Abuelnasr, 2010;Farahani et al, 2010;Ahmed et al, 2010;Kunanoppadon, 2010;Helmy and El- Taweel, 2010;Qutbodin, 2010;Pattanasethanon, 2010;Fen et al, 2011;Thongwan et al, 2011; Theansuwan and Triratanasirichai, 2011; Al Smadi, 2011; Tourab et al, 2011; Raptis et al, 2011; Momani et al, 2011; Ismail et al, 2011; Anizan et al, 2011; Tsolakis and Raptis, 2011; Abdullah et al, 2011; Kechiche et al, 2011; Ho et al, 2011; Rajbhandari et al, 2011; Aleksic and Lovric, 2011; Kaewnai and Wongwises, 2011; Idarwazeh, 2011; Ebrahim et al, 2012; Abdelkrim et al, 2012; Mohan et al, 2012; Abam et al, 2012; Hassan et al, 2012; Jalil and Sampe, 2013; Jaoude and El-Tawil, 2013; Ali andShumaker, 2013;Zhao, 2013;El-Labban et al, 2013;Djalel et al, 2013; Nahas and Kozaitis, 2013;Petrescu and Petrescu, 2014a;2014b;2014c;2014d;2014e;2014f;2014g;2014h;2014i;2015a;2015b;2015c;2015d;2015e;Fu et al, 2015; Al-Nasra et al, 2015; Amer et al, 2015;Sylvester et al, 2015b;Kumar et al, 2015;Gupta et al, 2015;Stavridou et al, 2015b;Ge and Xu, 2015;Moretti, 2015;Wang et al, 2015).…”
mentioning
confidence: 99%